Ubuntu network Platform for Networking System Students (NetSys OS) - Mohamed Azaman, Nor Amelina Natasya; Mohamed Azaman, Nor Amelina Natasya (Journal of Computing Technologies and Creative Content, 2019)
Nowadays, the networking students don’t have any operating system that focuses for learning section. Moreover, studies related to the ability for the students navigate the type of platform operating system between Window and Linux are scant. This research aims to develop an operating system that be able to integrate with networking tools based on Ubuntu. The project has installed with the necessary software needed throughout the Networking System Course, new Graphical User Interface and has developed Live USB distributions to simplify the installation process. This project can eliminate licensing cost software and save time to download required tools by the networking student of University Kuala Lumpur Malaysian Institute Information Technology (UniKL MIIT). Verification & Validation model is used in this research to develop this project because it is related to develop a software or application step by phase and do the clear requirement analysis that needed from networking students. User Testing is implemented during testing phase to measure of how this project can meet the requirement by the networking students. Extensive formal documentation and guideline to use NetSys Operating System were developed to improve the student’s experience.